Advanced cell-based high-throughput screening assays targeting active and latent Mycobacterium tuberculosis - Shurpali, Ketaki Dilip; Singh, Upasana; Sarkar, Shamim Akhtar Sampa; Mishra, Abhishek; Kulkarni, Roshan; Joshi, Swati P.; Sarkar, Dhiman (Journal of Biotechnology, 2014)
European Biotechnology Congress, Lecce, ITALY, MAY 15-18, 2014

Antimicrobial activity of plant extracts against sexually transmitted pathogens - Jadhav, Nutan; Kulkarni, Sangeeta; Mane, Arati; Kulkarni, Roshan; Palshetker, Aparna; Singh, Kamalinder; Joshi, Swati P.; Risbud, Arun; Kulkarni, Smita (Natural Product Research, 2015)
Comprehensive management of sexually transmitted infections (STIs) using vaginal or rectal microbicide-based intervention is one of the strategies for prevention of HIV infection. Herbal products have been used for treating STIs traditionally. Herein, we present in vitro activity of 10 plant extracts and their 34 fractions against three sexually transmitted/reproductive tract pathogens - Neisseria gonorrhoeae, Haemophilus ducreyi and Candida albicans. The plant parts were selected; the extracts/fractions were prepared and screened by disc diffusion method. The minimum inhibitory and minimum cidal concentrations were determined. The qualitative phytochemical analysis of selected extracts/fractions showing activity was performed. Of the extracts/fractions tested, three inhibited C. albicans, ten inhibited N. gonorrhoeae and five inhibited H. ducreyi growth. Our study demonstrated that Terminalia paniculata Roth. extracts/fractions inhibited growth of all three organisms. The ethyl acetate fraction of Syzygium cumini Linn. and Bridelia retusa (L.) Spreng. extracts was found to inhibit N. gonorrhoeae at lowest concentrations.
Keywords: anti-STI activity; Candida albicans; fractions; Haemophilus ducreyi; microbicide; Neisseria gonorrhoeae; plant extracts